Selective hydrogenation of furfural using a membrane reactor. Issue 1 (30th November 2021) - Delima, Roxanna S.; Stankovic, Mia D.; MacLeod, Benjamin P.; Fink, Arthur G.; Rooney, Michael B.; Huang, Aoxue; Jansonius, Ryan P.; Dvorak, David J.; Berlinguette, Curtis P.
Abstract : Electrocatalytic palladium membrane reactors (ePMRs) use electricity and water to drive hydrogenation reactions without forming H2 gas. Abstract : Electrocatalytic palladium membrane reactors (ePMRs) use electricity and water to drive hydrogenation reactions without forming H2 gas. In these reactors, a hydrogen-permeable palladium foil physically separates electrochemical proton generation in aqueous media from chemical hydrogenation in organic media. We report herein the use of the ePMR to electrolytically hydrogenate furfural, an important biomass derivative. This system was proven to convert furfural into furfuryl alcohol and tetrahydrofurfuryl alcohol with 84% and 98% selectivities, respectively. To reach these high selectivities, we designed and built an ePMR for high-throughput testing. Using this apparatus, we tested how different solvents, catalysts, and applied currents impacted furfural hydrogenation. We found that bulky solvents with weak nucleophilicities suppressed the formation of side products. Notably, these types of solvents are not compatible with standard electrochemical hydrogenation architectures where electrolysis and hydrogenation occur in the same reaction chamber. This work highlights the utility of the ePMR for selective furfural hydrogenation without H2 gas, and presents a possible pathway for helping to decarbonize the hydrogenation industry.